Innovative Internet of Things-based Integrated Liquid Waste Monitoring for Sustainable Batik Industry - Qodri, Muhammad Fatih; Pratama, Bagus Gilang; Yuliani, Oni; Permana, Irvan Ardhi (Universitas Ahmad Dahlan, 2024)
Background: Batik, a UNESCO-recognized art form, experiences rising production demands. However, traditional waste disposal methods pollute waterways and degrade soil. This study addresses this concern. Contribution: We implemented an Internet of Things (IoT)-based liquid waste monitoring system in CV Smart Batik Indonesia to promote a green economy and sustainable practices. The system monitors critical waste parameters (temperature, pH, TDS, DO, turbidity) in real-time. Method: We integrated sensors to collect waste data, which is then transmitted through an internet network for monitoring. Results: The system offers automated monitoring with notifications via a website or mobile application while ensuring data confidentiality through Wireguard protection. Conclusion: This community service activity demonstrates the effectiveness of IoT-based monitoring systems in promoting sustainable batik production by ensuring compliance with environmental standards and reducing human workload in waste monitoring